An NADH-selective and sensitive fluorescence probe to evaluate living cell hypoxic stress. Issue 46 (11th November 2021) - Li, Mingzhe; Liu, Chang; Zhang, Wenjuan; Xu, Longfei; Yang, Miaomiao; Chen, Zhaoli; Wang, Xinxing; Pu, Lingling; Liu, Weili; Zeng, Xianshun; Wang, Tianhui
Abstract : Cellular disease and senescence are often accompanied by an imbalance in the local oxygen supply. Abstract : Cellular disease and senescence are often accompanied by an imbalance in the local oxygen supply. Under hypoxia, mitochondrial NADH and FADH2 cannot be oxidized by the mitochondrial electron transport chain, which leads to the accumulation of reducing equivalents and subsequent reduction stress. Detecting changes in intracellular NADH levels is expected to allow an assessment of stress. We synthesized a red fluorescent probe, DPMQL1, with high selectivity and sensitivity for detecting NADH in living cells. The probe DPMQL1 has strong anti-interference abilities toward various potential biological interferences, such as metal ions, anions, redox species, and other biomolecules. In addition, its detection limit can reach the nanomolar level, meaning it can display small changes in NADH levels in living cells, so as to realize the evaluation of cell-based hypoxic stress.